The Influence of Social Media Usage and Political Trust on Young Voters Political Participation in Padang City - Muhammad Arrazak; M. Adnan (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2025)
The advancement of information technology and evolving political dynamics have significantly changed how young people engage in politics. This study focuses on investigating the influence of social media usage and political trust on the political involvement of Generation Z and Millennials in the 2024 election in Padang City. The research, utilizing a quantitative associative method with multiple linear regression analysis, involved 100 respondents aged 17 to 42, selected through proportional stratified random sampling. The results revealed a notable simultaneous influence of social media usage and political trust on political participation, accounting for 31.6%. Individually, social media usage had a substantial influence of 29.5%, while political trust had an 8.6% impact on political participation. Based on these findings, recommended that the government and relevant institutions enhance digital and political literacy among young people and foster political trust through transparency and accountability. This research emphasizes the significance of effective political communication strategies on social media to boost the political engagement of young individuals in future elections.